The influence of Micephyt preparation on seed productivity and on qualtity of hybrid seeds of Cucurbita pepo var. giramontia Duch - V. F. Khlebnikov; N. V. Smurova; N. V. Smurova; I. T. Balashova (Овощи России)
Relevance. Biologically active compounds are widely used at the modern vegetable production, and especially at the seed production. Influence of Micephyt preparation in the mixed with Etrel is evaluated at the first time. The goal of the study is evaluation the effect of Micephyt in the mixed of Etrel on the obtaining of hybrid seeds of the squash (Cucurbita pepo var. giramontia Duch.).Materials and methods. Studies were carried out at the experimental plot Transnistrian State University named T.G. Shevchenko (Tiraspol) during 2010-2012. The object of studies was maternal line F1 (166/5x98/5) of squash (analog of commercial hybrid F1 Lenutsa). Materials of study were preparations: Etrel (c= 0 and 300 ppm) and Micephyt in the mixed with Etrel (c= 10 and 100 ppm). There were 2 treatments of squash plants with these preparations: at the stage 2-3 leaves, and at the stage of 6-7 leaves.Results. Treatments maternal line of squash F1 with mixed preparation “Etrel-300 ppm + Micephyt-10 ppm” show the positive effect on the seed productivity of plants. We observed the significant increasing main components of seed productivity during three years of study. The mass of 1000 seed was increased on 10.1%; the quantity of seed fruits was increased on 9.0%; the quantity of fruits on the plant was increased on 11.8% and the seed productivity was increased on 33.0%. Seed yields of F1 squash were increased in 1.37 times on the standard (“Etrel-300 ppm”) after plant treatment with mixed preparation “Etrel-300 ppm + Micephyt-10 ppm”. High quality of seeds was maintained. The profitability of additional costs associated with the use of the preparation Micephit for the treatment of the maternal line 166/5 squash was 343%. So, the treatment of squash plants with mixed preparation “Etrel-300 ppm + Micephyt-10 ppm” is economic effective element the technology of F1 squash hybrid seed production.